‘Let Your Servant Depart in Peace’: Seventeenth-Century Eucharistic Preparation as Ars Moriendi - Tarnasky, Will (Reformation & Renaissance review, 2022)
There was a ubiquitous association between death and the Eucharist in the early modern English Protestant imagination, as revealed in the remarkably understudied body of English pre-Communion handbooks. These books, published by both men and women, across confessional boundaries, led readers through highly methodical meditations to prepare them to worthily receive the Sacrament of Communion. Eucharistic handbooks and Ars Moriendi literature were both widely and enthusiastically received in the seventeenth century and they were closely connected. Divines who published Ars Moriendi tracts also penned a preparatory manual, and this essay will show how in the seventeenth century these genres, and the devotional practices they prescribed, began to blend into one another. Sacramental preparation became a conscious preparation for death and the newer, seventeenth-century art of worthy receiving was absorbed into the already well-established art of dying.